Anomalous Magnetic Moment of Muon in Economical 3-3-1 Model - Binh, Dinh Thanh; Huong, Do Thi; Hue, Le Tho; Long, Hoang Ngoc (Communications in Physics, 2015)
We investigate in detail one-loop contribution of new particles to the muon anomalous magnetic moment \((g-2)_μ\) in the framework of the economical 3-3-1 model. The main contributions to the anomalous magnetic moment come from new neutral gauge boson \(Z’\), bilepton singly charged vector boson Y^±. The contributions of new neutral/charged scalars are small and can be neglected. The result is extended to other versions of 3-3-1 models. Comparing the anomalous magnetic moment value in this model with experimental value we set the extension requirement for the model